Pengaruh Latihan Depth Jump Terhadap Daya Ledak Otot Tungkai Pemain Bola Voli SMK Negeri 3 Bengkulu Selatan - Biy Paidul S; Dolly Apriansyah; Dody Ertanto (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of depth jump training on the explosive power of leg muscles in volleyball players at SMKN 3 Bengkulu Selatan. A total sampling method was used to determine the number of respondents, resulting in 13 student volleyball players at SMKN 3 Bengkulu Selatan. This experimental study employed a One Group Pretest-Posttest design, a pre-experimental design that includes a pretest (test before treatment) and a posttest (test after treatment) within one group. Data collection used test scores. Descriptive data analysis techniques and t-tests were used. The results of this study indicate an effect of depth jumps on the explosive power of volleyball players at SMKN 3 Bengkulu Selatan, with a calculated t-value of 2.578 and a t-table of 1.782, with a significance level of α = 0.05 and dk = 12.